Pengaruh Influencer Marketing, Affiliate Marrketing, Product Display terhadap Impulsive Buying Pada Pengguna Tiktok Shop-Tokopedia (Study Kasus Mahasiswa Universitas Islam Malang Fakultas Ekonomi dan Bisnis Angkatan 2022). - Haidar S, M Hisam; Wahono, Budi; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the influence of influencer marketing, affiliate marketing, and product display on impulsive buying among TikTok Shop–Tokopedia users, specifically students from the Islamic University of Malang, class of 2022. The research is motivated by the increasing trend of impulsive buying among younger generations, driven by the rise of social media–based e-commerce platforms such as TikTok, which integrate entertainment with digital marketing. A quantitative approach with an explanatory research method was employed. The study involved 120 respondents selected through purposive and snowball sampling techniques. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression. The findings reveal that influencer marketing, affiliate marketing, and product display collectively have a significant effect on impulsive buying. Furthermore, each variable individually has a positive and significant impact on impulsive buying. These results highlight the important role of social media–based digital marketing strategies in fostering impulsive buying behavior on the TikTok Shop–Tokopedia platform among university students. Keywords: Influencer Marketing, Affiliate Marketing, Display Product, And Impulsive Buying.